Pattern and appropriateness of antibiotic therapy for acute respiratory tract infection among under-five children accessing care in a tertiary facility, Sokoto, Nigeria - Fatima Ishaq Abubakar; Hadiza Kubra Ahmed; Omotolani Olawunmi Akintunde; Idrees Abiodun Rufai (BMJ Paediatrics Open)
Introduction Acute respiratory tract infections (ARIs) are a major cause of antibiotic use among under-five (U5) children, often leading to inappropriate prescriptions that contribute to antimicrobial resistance, adverse drug reactions and higher healthcare costs.Objectives To assess the pattern and rate of antibiotic prescriptions and evaluate their appropriateness based on WHO and Paediatric Association of Nigeria guidelines for ARI treatment among U5 children at Usmanu Danfodiyo University Teaching Hospital, SokotoMethods A retrospective review of medical records (case folders and prescription sheets) was conducted for U5 children diagnosed with ARI over a 10-month period at the paediatric outpatient and inpatient units, Department of Paediatrics, UDUTH. Data extracted included patient sociodemographic characteristics, ARI diagnosis based on Integrated Management of Childhood Illnesses/WHO criteria and antibiotic/medication details (class, name, route, dose, frequency, duration and regimen). Analysis was performed using SPSS V.20.0; p<0.05 was considered statistically significant.Results A total of 2140 drugs and 1545 antibiotics were prescribed, averaging 2.2 and 1.6 per patient, respectively. Upper respiratory tract infections accounted for 66.2% of antibiotic indications. The antibiotic prescription rate was 100.0 %, with 71.0% administered parenterally. Most prescriptions used generic names (96.5%) and were listed in the National Essential Medicines List (100%). Cephalosporins were most frequently prescribed (46.4%), followed by penicillins; fluoroquinolones were least prescribed (1.2%). Mono-antibiotic therapy was used in 53.2% of cases. Notably, 81.5% of prescriptions came from second-line therapies. Appropriate prescribing was observed for duration (93.6%), dose (66.0%), frequency (69.7%) and indication/choice (66.5%).Conclusion Despite encouraging adherence to appropriate antibiotic dosage regimen, the high rate of antibiotic prescription, parenteral antibiotic administration and alternative antibiotic use highlights ongoing concerns with risk of resistance, adverse effects and treatment failure. Strengthening antibiotic stewardship and adherence to first-line guidelines is crucial to optimise ARI treatment in resource-limited settings.